Viljens frihed og ufrihed i ældre luthersk tradition - Olsen, Peter (Dansk Teologisk Tidsskrift, 2017)
Martin Luther and early Lutheran tradition claimed that God wills both life and death. There is, however, an asymmetry between God’s will for life and God’s will for death. The article explores how this asymmetry has been handled in different ways within the early Lutheran tradition. Also, the Formula of Concord (1577) understood divine predestination to be the cause of human faith. Later Lutheran Orthodoxy understood human faith to be the reason for divine predestination. In the 1880’s these two positions gave rise to a controversy among North American Lutherans. Their main arguments are reproduced. Martin Luther himself believed that everything happened by necessity, but he understood this to be compatible with a distinct version of a free will. In modern philosophical parlance, Luther was a compatibilist. In this, later Lutheran Orthodoxy did not follow the reformer. It moved towards synergism.